PERUMUSAN KONSEP DALAM PROSES PERANCANGAN INTERIOR RUMAH TINGGAL - Yusuff, Adisti Ananda; Wiyono, Erina; Rochyat, Indra Gunara (Gorga : Jurnal Seni Rupa, 2024)
Nowadays, building a house is not only to be a shelter, but a house becomes a reflection of the status and social position of its occupants. reflection of the status and social standing of its occupants. In principle, interior designers have an effort to solve a problem that exists and is related to the interior of a room. related to the inside of a room. Interior designers can create a concept that is in accordance with the character and needs of the problems needed by residential users. The purpose of this research is as a guideline for formulating concepts in the design of residential interiors for the world of education in lectures. for the world of education in lectures. The method used in this This research is a qualitative method through a case study approach. By collecting data from the literature, the theory that will be used is obtained and then analyzed and represented to show the concept of interior design of residential houses for the world of education in lectures. then analyzed through 3 stages, namely potential research results by going through 3 stages, namely data reduction, data display, and verification. data, and verification. The result of this research is a formulation of concepts in the form of strategic stages of division of the stages of analysis, synthesis, and evaluation for designers and students to be stages of analysis, synthesis, and evaluation for designers and students to be a reference in making residential design concepts. concept of residential design. In addition, this research can also used as a reference for the stages in implementation in determining the concept of interior design of a residential house.Keywords: conceptualization, interior design, residentialAbstrakSaat ini membangun sebuah rumah tinggal bukan hanya untuk menjadi tempat berlindung saja, namun rumah tinggal menjadi sebuah cerminan dari status dan kedudukan sosial penghuninya. Secara prinsip, desainer interior memiliki upaya untuk memecahkan sebuah permasalahan yang ada dan berkaitan dengan bagian dalam sebuah ruangan. Desainer interior dapat membuat sebuah konsep yang sesuai dengan karakter dan kebutuhan atas permasalahan yang dibutuhkan oleh pengguna rumah tinggal. Tujuan dari penelitian ini adalah sebagai pedoman untuk merumuskan konsep dalam perancangan interior rumah tinggal bagi dunia Pendidikan didalam perkuliahan. Metode yang digunakan dalam penelitian ini merupakan metode kualitatif melalui pendekatan studi kasus. Dengan mengumpulkan data dari litelatur didapatkan teori yang akan digunakan yang terkait kemudian dilakukan analisis melalui 3 tahap yaitu reduksi data, display data, dan verivikasi. Hasil pada penelitian ini merupakan sebuah perumusan konsep berupa tahapan strategi pembagian tahapan analisis, sintesis, dan evaluasi bagi desainer dan juga mahasiswa untuk menjadi acuan dalam pembuatan konsep perancangan rumah tinggal. Selain itu penelitian ini juga dapat dijadikan sebagai acuan tahapan dalam pelaksanaan dalam menentukan konsep perancangan interior rumah tinggal.Kata Kunci: konseptualisasi, desain interior, rumah tinggalAuthors:Adisti Ananda Yusuff : Universitas Esa UnggulErina Wiyono : Universitas Esa UnggulIndra Gunara Rochyat : Universitas Esa Unggul ReferencesAdiluhung, H. (2021). Proses Kreatif Tim Desainer Rancang Bangun Kendaraan Tempur Kelas Ringan Pt Pindad. Gorga¯: Jurnal Seni Rupa, 10(1), 10. https://doi.org/10.24114/gr.v10i1.20741Andeska, N., & Rahmawati, R. (2021). Kajian Estetika Pada Rumah Adat Aceh Besar Taman Ratu Safiatuddin. Gorga¯: Jurnal Seni Rupa, 10(1), 80. https://doi.org/10.24114/gr.v10i1.24736Cahyani, S. D., Poerwoningsih, D., & Wahjutami, E. L. (2019). KONSEP HUNIAN ADAPTIF SEBAGAI UPAYA PENANGANAN RUMAH TINGGAL TIDAK LAYAK HUNI TERHADAP RESISTENSI PENYAKIT INFEKSI. Mintakat: Jurnal Arsitektur, 20(2), 83“95. https://doi.org/10.26905/mj.v20i2.3800Ching, F. D. K., & Binggeli, C. (2012). Interior Desing Illustrated (3rd ed.). y John Wiley & Sons, Inc., Hoboken, New Jersey.Miles, M. B., Huberman, A. M., & Saldana, J. (2014). Qualitative Data Analisys (Helen Salmon (ed.); 3rd ed.). SAGE Publications.Santosa, A. (2014). PENDEKATAN KONSEPTUAL DALAM PROSES PERANCANGAN INTERIOR. Dimensi Interior, 3(2).Sunarmi. (2013). Pendekatan Pemecahan Desain Interior Rumah Tinggal. Ornamen, 10(1), 41“56.Wicaksono, A. A., & Tisnawati, E. (2014). Teori interior. Griya Kreasi.